Medical magnesium alloy with high toughness, antibacterial property and non-toxicity as well as preparation method and application of medical magnesium alloy
By adding appropriate amounts of bismuth and zinc to the medical magnesium alloy and performing optimization process treatment, high-strength, tough, antibacterial and non-toxic medical magnesium alloys are prepared, which solves the problem of rapid infection and degradation of existing magnesium alloys after implantation, achieving more stable implantable materials and broader application prospects.
Patent Information
- Application Number
- CN202510008549.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-03-28
AI Technical Summary
Existing medical magnesium alloys are prone to infection, poor strong plasticity, fast degradation after implantation, affecting their stability and application effects.
By adding appropriate amounts of bismuth and zinc to the magnesium alloy and optimizing regulation, a high-strength, tough, antibacterial and non-toxic medical magnesium alloy is prepared. The chemical composition of the alloy is Bi: 0.4%~2.2%, Zn: 0.4%~2.2%. Through specific process flows, such as smelting, homogenization treatment and extrusion processing, its strength and antibacterial properties are improved.
It significantly improves the strength and toughness of magnesium alloy, enhances its antibacterial properties, reduces the risk of infection, and effectively controls its degradation rate, improving the stability and application effect of implanted materials.
Smart Images

Figure CN119710404A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of magnesium alloys, and relates to a high-strength, tough, antibacterial and non-toxic medical magnesium alloy, and also relates to a manufacturing method and application of the medical magnesium alloy. Background Art
[0002] Traditional medical implant materials that are widely used at present, such as stainless steel, titanium and titanium alloys, lack antibacterial properties because the surface of the implant materials is conducive to bacterial adhesion, colonization and biofilm formation, which in turn leads to postoperative infection or bone tissue dissolution, which is a major cause of implant material failure or even implant failure. In addition, due to their higher elastic modulus, these implant materials differ greatly from the elastic modulus of natural bones, which will cause stress shielding effect during implantation, thus affecting the bone healing process. Since these implant materials degrade very slowly in the human body, after the patient's bones heal, a second operation is still required to remove the implant, which increases the patient's pain and economic burden.
[0003] Magnesium alloys are ideal for biodegradable medical implant materials due to their low density, high specific strength and specific stiffness, elastic modulus close to that of human bones, and excellent biocompatibility. They have shown broad application prospects in medical fields such as orthopedics, cardiovascular and dentistry. However, as biodegradable medical implant materials, magnesium alloys still face problems such as post-implantation infection, poor strength and plasticity, and rapid degradation. Although the infection can be solved through drug treatment or surgery, patients have to bear additional pain and economic burden.
[0004] Non-toxic magnesium-bismuth alloys demonstrate great potential for material development. The addition of bismuth (Bi) not only forms a thermally stable Mg3Bi2 phase, thereby improving the formability and strength of the alloy, but also gives the alloy anti-inflammatory, antibacterial and other biological activities. Bismuth compounds have been used in the medical field for about 200 years. In addition, the addition of bismuth helps to refine the grains of magnesium alloys and improve the strength and plasticity of the material, while grain refinement also indirectly improves the corrosion resistance of the alloy. Smaller grains can cause the alloy to exhibit more uniform corrosion behavior. Although binary magnesium-bismuth alloys have good biocompatibility, their mechanical support is still insufficient compared to the healing cycle of bone tissue, which may affect the stability of implant materials.
[0005] Zinc (Zn) is an essential trace element for the human body and has important physiological functions, such as promoting bone growth, accelerating wound healing, and enhancing immune function. In the body environment, zinc can regulate the degradation rate of the alloy to ensure that the material provides sufficient mechanical support during bone healing or tissue repair. In addition, zinc ions have a regulatory effect on bone cells (such as osteoblasts and osteoclasts), which can promote the proliferation and differentiation of osteoblasts, thereby promoting bone tissue regeneration. At present, there have been relevant reports on the research of magnesium-bismuth-zinc alloys, demonstrating their potential application value as biomedical materials.
[0006] At present, the antibacterial effect of magnesium alloys mainly depends on their degradation process in the human body. As magnesium alloy implant materials degrade, the increase in magnesium ion concentration, local pH value and hydrogen evolution amount forms a highly alkaline environment, thereby inhibiting the normal growth of bacteria and achieving an antibacterial effect. Magnesium ions change the polarization state of bacterial cell membranes, interfere with the transport of essential substances for bacteria, lead to the inactivation of enzymes in bacteria, and then affect the normal biochemical reactions of bacteria, causing energy and material metabolism disorders of bacteria, thereby inhibiting their growth. In addition to magnesium ions, other alloying elements in magnesium alloys such as zinc (Zn) and bismuth (Bi) also have antibacterial and anti-inflammatory effects. However, the degradation rate of the alloy should not be too fast. Too fast degradation will cause the implant material to lose its support function prematurely, and higher ion concentrations and high alkaline environments may induce cytotoxicity. Therefore, how to improve the strength and plasticity of magnesium alloys while maintaining antibacterial properties and effectively control their degradation rate is a key issue in the current research on biodegradable magnesium alloy materials. Summary of the invention
[0007] The first purpose of the present invention is to provide a medical magnesium alloy with high strength, toughness, antibacterial and non-toxicity. By adding bismuth and zinc to magnesium to form an alloy, and optimizing and regulating the content of bismuth and zinc, the prepared magnesium alloy can maintain its antibacterial properties while improving the strength and plasticity of the magnesium alloy and effectively controlling its degradation rate.
[0008] The second object of the present invention is to provide a method for preparing the above-mentioned high-strength, toughness, antibacterial and non-toxic medical magnesium alloy.
[0009] The third object of the present invention is to provide the application of the above-mentioned high-strength, toughness, antibacterial and non-toxic medical magnesium alloy.
[0010] The first technical solution adopted by the present invention is that the high-strength, toughness, antibacterial and non-toxic medical magnesium alloy includes the following components by mass percentage: Bi: 0.4%~2.2%, Zn: 0.4%~2.2%, and the rest is Mg and inevitable impurities.
[0011] The present invention is also characterized in that, in terms of mass percentage, the chemical composition is as follows: Bi: 1.97%, Zn: 2.01%, and the rest is Mg and inevitable impurities. The second technical solution adopted by the present invention is a method for preparing a high-strength, tough, antibacterial and non-toxic medical magnesium alloy, and the specific steps are as follows: S1. According to the mass percentage, 0.4~2.2% of bismuth particles and 0.4~2.2% of zinc particles are weighed, and the rest is magnesium ingot, and the raw materials are polished to remove the surface oxide film; S2. The crucible is placed in a resistance furnace for preheating, and the magnesium ingot, bismuth particles and zinc particles are added to the preheated crucible, and the crucible is heated until the metal is completely melted, stirred, and then slag is removed after standing, and then the slag is quickly cast after the slag is removed, and after solidification, it is quickly quenched in ice water to obtain a magnesium alloy ingot, and a mixed gas of sulfur hexafluoride and argon is introduced throughout the process; S3. The magnesium alloy ingot is subjected to wire cutting, and then subjected to homogenization heat treatment, followed by quenching in water to obtain a heat-treated magnesium alloy; S4. The heat-treated magnesium alloy is placed in an extruder for extrusion processing, and quenched after extrusion to obtain a medical magnesium alloy.
[0012] The present invention is also characterized in that: The purity of magnesium ingots in S1 is ≥99.99%, the purity of bismuth particles is ≥99.999%, and the purity of zinc particles is ≥99.99%.
[0013] S2 is operated under the protection of a mixed gas of sulfur hexafluoride and argon in a ratio of 0.5:99.5. The magnesium ingot, bismuth particles and zinc particles are added to the preheated crucible, and then the resistance furnace temperature is heated to 730~750℃ to melt the magnesium ingot, bismuth particles and zinc particles. The mixture is stirred for 3~5 times for a total of 8~12 minutes. After stirring, the temperature is controlled at 720~740℃ and allowed to stand for 20~30 minutes. The mixture is then deslagging and cast at 710~720℃. After solidification, the ingot is quenched in ice water at 0~4℃ to obtain a magnesium alloy ingot.
[0014] The conditions of homogenization heat treatment in S3 are: 480~500℃, holding time is 4~5h, followed by quenching in water at 10~25℃.
[0015] The extrusion processing conditions in S4 are: keeping warm in a box furnace at 200~230℃ for 30~35min, extrusion ratio of 18:1, extrusion speed of 1~2.4mm / s, and quenching the obtained extruded rod in water at 10~25℃.
[0016] The third technical solution adopted by the present invention is the application of high-strength, toughness, antibacterial and non-toxic medical magnesium alloy, which is used in bone nails, bone plates, intramedullary nails, bone filling materials, vascular stents, oral repair stents and other devices.
[0017] The beneficial effects of the present invention are: (1) The medical magnesium alloy prepared by the present invention is subjected to a trace alloying treatment, a trace amount of bismuth and zinc elements are added, and the high purity of the alloy is ensured. The subsequent homogenization and extrusion treatment is used for tissue regulation, which significantly improves the strength and toughness of the magnesium alloy, making its mechanical properties in medical implants more compatible with the requirements of human bone tissue, and reducing the risk of early failure caused by insufficient strength; (2) The medical magnesium alloy prepared by the present invention introduces bismuth and zinc, which have antibacterial effects, and can effectively inhibit the growth of common pathogens (such as Escherichia coli), reduce the risk of infection after implantation, and also avoid the side effects of antibiotic use; (3) The present invention achieves an effective balance between the mechanical properties, corrosion resistance and antibacterial properties of the alloy by optimizing the alloy composition, processing technology and conditions. The bismuth content is controlled at 0.5% to 2%, which can ensure the generation of a small amount of Mg3Bi2 phase, thereby improving the strength without affecting the corrosion resistance. Trace zinc can regulate the degradation rate, ensuring that the material provides sufficient mechanical support during bone healing or tissue repair. Zinc can also promote the proliferation and differentiation of bone cells, which helps bone tissue regeneration. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a metallographic microstructure diagram of the biomedical magnesium alloy prepared in Example 1 of the present invention; Figure 2 This is a metallographic microstructure diagram of the biomedical magnesium alloy prepared in Example 2 of the present invention; Figure 3 This is a metallographic microstructure diagram of the biomedical magnesium alloy prepared in Example 3 of the present invention; Figure 4 This is a physical picture of the Escherichia coli colony distribution of the biomedical magnesium alloy prepared in Example 3 of the present invention; Figure 5 This is a fluorescence staining image of cell co-culture of the biomedical magnesium alloy prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0019] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0020] The high-strength, toughness, antibacterial and non-toxic medical magnesium alloy includes the following components by mass percentage: Bi: 0.4%~2.2%, Zn: 0.4%~2.2%, and the rest is Mg and inevitable impurities.
[0021] Further preferably, the chemical composition, by mass percentage, is as follows: Bi: 1.97%, Zn: 2.01%, and the remainder is Mg and unavoidable impurities.
[0022] The preparation method of high-strength, toughness, antibacterial and non-toxic medical magnesium alloy has the following specific steps: S1. According to the mass percentage, 0.4~2.2% of bismuth particles and 0.4~2.2% of zinc particles are weighed, and the rest is magnesium ingot, and the raw materials are polished to remove the surface oxide film; Among them, the purity of magnesium ingots is ≥99.99%, the purity of bismuth particles is ≥99.999%, and the purity of zinc particles is ≥99.99%.
[0023] S2. The crucible is placed in a resistance furnace for preheating, and the magnesium ingot, bismuth particles and zinc particles are added to the preheated crucible, and the crucible is heated until the metal is completely melted, stirred, and then slag is removed after standing, and then the slag is quickly cast after the slag is removed, and after solidification, it is quickly quenched in ice water to obtain a magnesium alloy ingot, and a mixed gas of sulfur hexafluoride and argon is introduced throughout the process; The whole process is operated under the protection of a mixed gas of sulfur hexafluoride and argon in a ratio of 0.5:99.5. The magnesium ingot, bismuth particles and zinc particles are added to the preheated crucible, and then the resistance furnace temperature is heated to 730-750°C to melt the magnesium ingot, bismuth particles and zinc particles. The mixture is stirred for 3-5 times for a total of 8-12 minutes. After stirring, the temperature is controlled at 720-740°C and allowed to stand for 20-30 minutes. The mixture is then deslagging and cast at 710-720°C. After solidification, the ingot is quenched in ice water at 0-4°C to obtain a magnesium alloy ingot.
[0024] S3. The magnesium alloy ingot is subjected to wire cutting, and then subjected to homogenization heat treatment, followed by quenching in water to obtain a heat-treated magnesium alloy; The conditions for homogenization heat treatment are: 480~500℃, holding time is 4~5h, followed by quenching in water at 10~25℃.
[0025] S4. The heat-treated magnesium alloy is placed in an extruder for extrusion processing, and quenched after extrusion to obtain a medical magnesium alloy.
[0026] The extrusion processing conditions are: keeping warm in a box furnace at 200-230°C for 30-35min, an extrusion ratio of 18:1, an extrusion speed of 1-2.4mm / s, and the obtained extruded rods are quenched in water at 10-25°C.
[0027] The high-strength, toughness, antibacterial and non-toxic medical magnesium alloy prepared according to the preparation method of the present invention is applied to bone nails, bone plates, intramedullary nails, bone filling materials, vascular stents, oral repair stents and other devices, but is not limited to the application in the above-mentioned fields, and can also be applied to other medical implant fields.
[0028] Example 1 This embodiment provides a biomedical magnesium alloy with high strength and toughness, antibacterial effect and non-toxicity, and the mass percentages of the alloy elements are: Zn is 0.43%, Bi is 2.01%, Mn is 0.002%, Fe is 0.002%, Ni is 0.0001%, Ca is 0.0001%, and the rest is Mg.
[0029] The raw materials are high-purity magnesium ingots (purity ≥99.99%), high-purity bismuth particles (purity ≥99.999%), and high-purity zinc particles (purity ≥99.99%).
[0030] S1. The raw materials of high-purity magnesium ingot, high-purity bismuth particles and high-purity zinc particles are polished to remove the oxide layer for standby use; S2. Raise the temperature of the vacuum melting furnace to 740°C, and under the protection of a mixed gas of sulfur hexafluoride and argon in a ratio of 0.5:99.5, weigh the corresponding mass of magnesium ingots according to the above mass percentage and add them to the preheated crucible. After the magnesium ingot is melted, add bismuth particles and zinc particles, wherein the actual amount of Mg added is 1.05 times the calculated amount, the actual amount of Bi added is 1.1 times the calculated amount, and the actual amount of Zn added is 1.05 times the calculated amount. Then lower the temperature of the vacuum melting furnace to 725°C, and after all the raw materials are melted, stir for 12 minutes in three times, let it stand for 20 minutes after stirring, remove the surface oxides and impurities by slag removal, and then cool to 710°C for casting to obtain an ingot. After the ingot cools, put the ingot into ice water at 4°C for quenching.
[0031] S3. The cylindrical samples obtained above were cut into 35 mm in height and 30 mm in diameter, and homogenized in a box-type resistance furnace. After the temperature of the box-type resistance furnace was raised to 480°C, the alloy samples were added and kept warm for 5 hours, and then quenched in 20°C water.
[0032] S4. After homogenization treatment, the alloy sample was placed in a resistance furnace at 200°C for 30 minutes, and then placed in an extrusion die. Extrusion deformation was completed on an extruder with an extrusion speed of 1 mm / s and an extrusion ratio of 18:1. It was extruded into a rod with a diameter of 7 mm. The obtained extruded rod was quenched in water at 25°C.
[0033] The yield strength of the magnesium alloy material of Example 1 at room temperature is 325.5 MPa, the tensile strength is 362.4 MPa, and the elongation is 18.5%. The corrosion rate is 1.16 mm / y, and the antibacterial rate against Escherichia coli reaches 98.2%. No dead cells are found in cell fluorescence staining, indicating that Example 1 is non-toxic to cells.
[0034] Example 2 This embodiment provides a biomedical magnesium alloy with high strength and toughness, antibacterial effect and non-toxicity, the mass percentage of the alloy elements is: Zn is 0.98%, Bi is 2.04%, Mn is 0.001%, Fe is 0.002%, Ni is 0.0001%, Ca is 0.0001%, and the rest is Mg.
[0035] The raw materials are high-purity magnesium ingots (purity ≥99.99%), high-purity bismuth particles (purity ≥99.999%), and high-purity zinc particles (purity ≥99.99%).
[0036] S1. The raw materials of high-purity magnesium ingot, high-purity bismuth particles and high-purity zinc particles are polished to remove the oxide layer for standby use; S2. Raise the temperature of the vacuum melting furnace to 730°C, and under the protection of a mixed gas of sulfur hexafluoride and argon, weigh the corresponding mass of magnesium ingots according to the above mass percentage and add them to the preheated crucible. After the magnesium ingot is melted, add bismuth particles and zinc particles, wherein the actual amount of Mg added is 1.05 times the calculated amount, the actual amount of Bi added is 1.1 times the calculated amount, and the actual amount of Zn added is 1.05 times the calculated amount. Then lower the temperature of the vacuum melting furnace to 720°C, and after all the raw materials are melted, stir for 10 minutes in three times, let it stand for 25 minutes after stirring, remove the surface oxides and impurities by slag removal, and then cool to 715°C for casting to obtain an ingot. After the ingot cools, put the ingot into 0°C ice water for quenching.
[0037] S3. The obtained samples are cut into cylindrical samples with a height of 35 mm and a diameter of 30 mm, and homogenized in a box-type resistance furnace. After the temperature of the box-type resistance furnace is raised to 500°C, the alloy sample is added and kept warm for 5 hours, and then quenched in 20°C water.
[0038] S4. After homogenization treatment, the alloy sample was placed in a resistance furnace at 230°C for 35 minutes, and then placed in an extrusion die. Extrusion deformation was completed on an extruder with an extrusion speed of 2 mm / s and an extrusion ratio of 18:1. It was extruded into a rod with a diameter of 7 mm. The obtained extruded rod was quenched in water at 10°C.
[0039] The yield strength of the magnesium alloy material of Example 2 at room temperature is 322.7 MPa, the tensile strength is 366.1 MPa, and the elongation is 16.6%. The corrosion rate is 1.18 mm / y, and the antibacterial rate against Escherichia coli reaches 96.2%. No dead cells are found in cell fluorescence staining, indicating that Example 2 is non-toxic to cells.
[0040] Example 3 This embodiment provides a biomedical magnesium alloy with high strength and toughness, antibacterial effect and non-toxicity, the mass percentage of alloy elements is: Zn is 2.01%, Bi is 1.97%, Mn is 0.002%, Fe is 0.001%, Ni is 0.0001%, Ca is 0.0002%, and the rest is Mg.
[0041] The raw materials are high-purity magnesium ingots (purity ≥99.99%), high-purity bismuth particles (purity ≥99.999%), and high-purity zinc particles (purity ≥99.99%).
[0042] S1. The raw materials of high-purity magnesium ingot, high-purity bismuth particles and high-purity zinc particles are polished to remove the oxide layer for standby use; S2. Raise the temperature of the vacuum melting furnace to 750°C, and under the protection of a mixed gas of sulfur hexafluoride and argon, weigh the corresponding mass of magnesium ingots according to the above mass percentage and add them to the preheated crucible. After the magnesium ingot is melted, add bismuth particles and zinc particles, wherein the actual amount of Mg added is 1.05 times the calculated amount, the actual amount of Bi added is 1.1 times the calculated amount, and the actual amount of Zn added is 1.05 times the calculated amount. Then lower the temperature of the vacuum melting furnace to 740°C, and stir for 8 minutes in three times after all the raw materials are melted, and let it stand for 25 minutes after stirring, remove the surface oxides and impurities, and then cool to 720°C for casting to obtain an ingot. After the ingot cools, put the ingot into 2°C ice water for quenching.
[0043] S3. The cylindrical samples obtained above were cut into 35 mm in height and 30 mm in diameter, and homogenized in a box-type resistance furnace. After the temperature of the box-type resistance furnace was raised to 490°C, the alloy samples were added and kept warm for 4.5 hours, and then quenched in 10°C water.
[0044] S4. After homogenization treatment, the alloy sample was placed in a resistance furnace at 210°C for 30 minutes, then placed in an extrusion die and extruded on an extruder. The extrusion speed was 1.1 mm / s and the extrusion ratio was 18:1. The extruded rods were quenched in water at 18°C.
[0045] The yield strength of the magnesium alloy material of Example 3 at room temperature is 321 MPa, the tensile strength is 399.8 MPa, and the elongation is 24.6%. The corrosion rate is 1.44 mm / y, and the antibacterial rate against Escherichia coli reaches 99.7%. No dead cells are found in cell fluorescence staining, indicating that Example 3 is non-toxic to cells.
[0046] Figures 1 to 3 The metallographic microstructure diagrams of the biomedical magnesium alloys prepared in Examples 1 to 3 respectively show that the alloy is completely recrystallized, the grain size is uniform, there are fewer second phase particles, and the uniformly distributed grains ensure the stability of the mechanical properties. At the same time, the smaller number of second phases improves the strength while having no effect on the corrosion resistance.
[0047] Figure 4 This is a physical picture of the Escherichia coli colony distribution of the biomedical magnesium alloy prepared in Example 3. It can be seen from the figure that there are almost no colonies after the Escherichia coli is cultured with the sample for 24 hours, indicating that the antibacterial effect of Example 3 is significant.
[0048] Figure 5 This is a fluorescence staining image of cell co-culture of the biomedical magnesium alloy prepared in Example 3. It can be seen from the image that no dead cells appear on the surface of the sample, indicating that the sample is non-toxic to cells.
[0049] Example 4 This embodiment provides a biomedical magnesium alloy with high strength and toughness, antibacterial effect and non-toxicity, the mass percentage of alloy elements is: Zn is 2.18%, Bi is 1.37%, Mn is 0.001%, Fe is 0.001%, Ni is 0.0001%, Ca is 0.0002%, and the rest is Mg.
[0050] The raw materials are high-purity magnesium ingots (purity ≥99.99%), high-purity bismuth particles (purity ≥99.999%), and high-purity zinc particles (purity ≥99.99%).
[0051] S1. The raw materials of high-purity magnesium ingot, high-purity bismuth particles and high-purity zinc particles are polished to remove the oxide layer for standby use; S2. Raise the temperature of the vacuum melting furnace to 740°C, and under the protection of a mixed gas of sulfur hexafluoride and argon, weigh the corresponding mass of magnesium ingots according to the above mass percentage and add them to the preheated crucible. After the magnesium ingot is melted, add bismuth particles and zinc particles, wherein the actual amount of Mg added is 1.05 times the calculated amount, the actual amount of Bi added is 1.1 times the calculated amount, and the actual amount of Zn added is 1.05 times the calculated amount. Then lower the temperature of the vacuum melting furnace to 730°C, and after all the raw materials are melted, stir for 11 minutes in three times, let it stand for 30 minutes after stirring, remove the surface oxides and impurities by slag removal, and then cool to 710°C for casting to obtain an ingot. After the ingot cools, put the ingot into ice water at 1°C for quenching.
[0052] S3. The cylindrical samples obtained above were cut into 35 mm in height and 30 mm in diameter, and homogenized in a box-type resistance furnace. After the temperature of the box-type resistance furnace was raised to 490°C, the alloy samples were added and kept warm for 4.5 hours, and then quenched in 18°C water.
[0053] S4. After homogenization treatment, the alloy sample was placed in a resistance furnace at 210°C for 30 minutes, then placed in an extrusion die and extruded on an extruder. The extrusion speed was 2.2 mm / s and the extrusion ratio was 18:1. The extruded rod was 7 mm in diameter and quenched in water at 20°C.
[0054] The yield strength of the magnesium alloy material of Example 4 at room temperature is 321.8 MPa, the tensile strength is 384.7 MPa, and the elongation is 20.6%. The corrosion rate is 1.32 mm / y, and the antibacterial rate against Escherichia coli reaches 96.4%. No dead cells are found in cell fluorescence staining, indicating that Example 4 is non-toxic to cells.
[0055] Example 5 The raw materials are the same as those in Example 3, and the preparation method is as follows: S1. The raw materials of high-purity magnesium ingot, high-purity bismuth particles and high-purity zinc particles are polished to remove the oxide layer for standby use; S2. Raise the temperature of the vacuum melting furnace to 745°C, and under the protection of a mixed gas of sulfur hexafluoride and argon, weigh the corresponding mass of magnesium ingots according to the above mass percentage and add them to the preheated crucible. After the magnesium ingot is melted, add bismuth particles and zinc particles, wherein the actual amount of Mg added is 1.05 times the calculated amount, the actual amount of Bi added is 1.1 times the calculated amount, and the actual amount of Zn added is 1.05 times the calculated amount. Then lower the temperature of the vacuum melting furnace to 735°C, and stir for 8 minutes in three times after all the raw materials are melted, and let it stand for 23 minutes after stirring, remove the surface oxides and impurities, and then cool to 720°C for casting to obtain an ingot. After the ingot cools, put the ingot into 4°C ice water for quenching.
[0056] S3. The cylindrical samples obtained above were cut into 35 mm in height and 30 mm in diameter, and homogenized in a box-type resistance furnace. After the temperature of the box-type resistance furnace was raised to 490°C, the alloy samples were added and kept warm for 4.5 hours, and then quenched in 15°C water.
[0057] S4. After homogenization treatment, the alloy sample was placed in a resistance furnace at 220°C for 30 minutes, then placed in an extrusion die and extruded on an extruder. The extrusion speed was 1.1 mm / s and the extrusion ratio was 18:1. The extruded rods were quenched in water at 18°C.
[0058] The yield strength of the magnesium alloy material of Example 5 at room temperature is 319 MPa, the tensile strength is 384.5 MPa, and the elongation is 23.3%. The corrosion rate is 1.09 mm / y, and the antibacterial rate against Escherichia coli reaches 99.4%. No dead cells are found in cell fluorescence staining, indicating that Example 5 is non-toxic to cells.
[0059] Example 6 This embodiment provides a biomedical magnesium alloy with high strength and toughness, antibacterial effect and non-toxicity, the mass percentage of alloy elements is: Zn is 0.9%, Bi is 1.35%, Mn is 0.002%, Fe is 0.001%, Ni is 0.0001%, Ca is 0.0001%, and the rest is Mg.
[0060] S1. The raw materials of high-purity magnesium ingot, high-purity bismuth particles and high-purity zinc particles are polished to remove the oxide layer for standby use; S2. Raise the temperature of the vacuum melting furnace to 735°C, and under the protection of a mixed gas of sulfur hexafluoride and argon, weigh the corresponding mass of magnesium ingots according to the above mass percentage and add them to the preheated crucible. After the magnesium ingot is melted, add bismuth particles and zinc particles, wherein the actual amount of Mg added is 1.05 times the calculated amount, the actual amount of Bi added is 1.1 times the calculated amount, and the actual amount of Zn added is 1.05 times the calculated amount. Then lower the temperature of the vacuum melting furnace to 720°C, and after all the raw materials are melted, stir for 10 minutes in three times, let it stand for 28 minutes after stirring, remove the surface oxides and impurities by slag removal, and then cool to 710°C for casting to obtain an ingot. After the ingot cools, put the ingot into 3°C ice water for quenching.
[0061] S3. The cylindrical samples obtained above were cut into 35 mm in height and 30 mm in diameter, and homogenized in a box-type resistance furnace. After the temperature of the box-type resistance furnace was raised to 480°C, the alloy samples were added and kept warm for 4 hours, and then quenched in 15°C water.
[0062] S4. After homogenization treatment, the alloy sample was placed in a resistance furnace at 220°C for 30 minutes, then placed in an extrusion die and extruded on an extruder. The extrusion speed was 1.1 mm / s and the extrusion ratio was 18:1. The extruded rod was 7 mm in diameter and quenched in water at 20°C.
[0063] The yield strength of the magnesium alloy material of Example 6 at room temperature is 320 MPa, the tensile strength is 367.4 MPa, and the elongation is 19.8%. The corrosion rate is 1.42 mm / y, and the antibacterial rate against Escherichia coli reaches 98.4%. No dead cells are found in cell fluorescence staining, indicating that Example 6 is non-toxic to cells.
[0064] In order to further verify the effect of adding different alloy components in the present invention, a comparative experiment was conducted.
[0065] Comparative Example 1 This comparative example provides a magnesium alloy, wherein the mass percentages of alloy elements are: Bi is 0.53%, Mn is 0.002%, Fe is 0.001%, Ni is 0.0001%, Ca is 0.0002%, and the rest is Mg, wherein the extremely small amounts of Mn, Fe, Ni, and Ca contained in the above components are all unavoidable impurities.
[0066] The raw materials are high-purity magnesium ingots (purity ≥ 99.99%) and high-purity bismuth particles (purity ≥ 99.999%).
[0067] S1. The raw materials of high-purity magnesium ingot and high-purity bismuth particles are polished to remove the oxide layer for standby use; S2. Raise the temperature of the vacuum melting furnace to 740°C, and under the protection of a mixed gas of sulfur hexafluoride and argon, weigh the corresponding mass of magnesium ingots according to the above mass percentage and add them to the preheated crucible. After the magnesium ingot is melted, add bismuth particles and zinc particles, wherein the actual amount of Mg added is 1.05 times the calculated amount, and the actual amount of Bi added is 1.1 times the calculated amount. Then lower the temperature of the vacuum melting furnace to 725°C, and after all the raw materials are melted, stir for 10 minutes in three times, let it stand for 20 minutes after stirring, remove the surface oxides and impurities by slag removal, and then cool to 710°C for casting to obtain an ingot. After the ingot cools, put it into ice water at 4°C for quenching.
[0068] S3. The cylindrical samples obtained above were cut into 35 mm in height and 30 mm in diameter, and homogenized in a box-type resistance furnace. After the temperature of the box-type resistance furnace was raised to 490°C, the alloy samples were added and kept warm for 4 hours, and then quenched in 20°C water.
[0069] S4. After homogenization treatment, the alloy sample was placed in a resistance furnace at 200°C for 30 minutes, then placed in an extrusion die and extruded on an extruder to complete the extrusion deformation. The extrusion speed was 1 mm / s and the extrusion ratio was 18:1. The sample was extruded into a rod with a diameter of 7 mm.
[0070] The yield strength of the magnesium alloy material of Comparative Example 1 at room temperature is 152.6MPa, the tensile strength is 180.2MPa, and the elongation is 29.1%. The corrosion rate is 1.64mm / y, and the antibacterial rate against Escherichia coli reaches 96.7%. No dead cells are found in cell fluorescence staining, indicating that Comparative Example 1 is non-toxic to cells.
[0071] Comparative Example 2 This comparative example provides a magnesium alloy, wherein the mass percentages of alloy elements are: Bi is 1.08%, Mn is 0.001%, Fe is 0.001%, Ni is 0.0001%, Ca is 0.0002%, and the remainder is Mg, wherein the extremely small amounts of Mn, Fe, Ni, and Ca contained in the above components are all unavoidable impurities.
[0072] The raw materials are high-purity magnesium ingots (purity ≥ 99.99%) and high-purity bismuth particles (purity ≥ 99.999%).
[0073] S1. The raw materials of high-purity magnesium ingot and high-purity bismuth particles are polished to remove the oxide layer for standby use; S2. Raise the temperature of the vacuum melting furnace to 740°C, and under the protection of a mixed gas of sulfur hexafluoride and argon, weigh the corresponding mass of magnesium ingots according to the above mass percentage and add them to the preheated crucible. After the magnesium ingot is melted, add bismuth particles and zinc particles, wherein the actual amount of Mg added is 1.05 times the calculated amount, and the actual amount of Bi added is 1.1 times the calculated amount. Then lower the temperature of the vacuum melting furnace to 725°C, and after all the raw materials are melted, stir for 10 minutes in three times, let it stand for 20 minutes after stirring, remove the surface oxides and impurities by slag removal, and then cool to 710°C for casting to obtain an ingot. After the ingot cools, put it into ice water at 4°C for quenching.
[0074] S3. The cylindrical samples obtained above were cut into 35 mm in height and 30 mm in diameter, and homogenized in a box-type resistance furnace. After the temperature of the box-type resistance furnace was raised to 480°C, the alloy samples were added and kept warm for 5 hours, and then quenched in 20°C water.
[0075] S4. After homogenization treatment, the alloy sample was placed in a resistance furnace at 200°C for 30 minutes, then placed in an extrusion die and extruded on an extruder to complete the extrusion deformation. The extrusion speed was 1 mm / s and the extrusion ratio was 18:1. The sample was extruded into a rod with a diameter of 7 mm.
[0076] The yield strength of the magnesium alloy material of Comparative Example 2 at room temperature is 144.4MPa, the tensile strength is 189.5MPa, and the elongation is 25.1%. The corrosion rate is 1.69mm / y, and the antibacterial rate against Escherichia coli reaches 83.2%. No dead cells are found in cell fluorescence staining, indicating that Comparative Example 2 is non-toxic to cells.
[0077] Comparative Example 3 This comparative example provides a magnesium alloy, wherein the mass percentages of alloy elements are: Bi is 1.94%, Mn is 0.001%, Fe is 0.002%, Ni is 0.0001%, Ca is 0.0001%, and the rest is Mg, wherein the extremely small amounts of Mn, Fe, Ni, and Ca contained in the above components are all unavoidable impurities.
[0078] The raw materials are high-purity magnesium ingots (purity ≥ 99.99%) and high-purity bismuth particles (purity ≥ 99.999%).
[0079] S1. The raw materials of high-purity magnesium ingot and high-purity bismuth particles are polished to remove the oxide layer for standby use; S2. Raise the temperature of the vacuum melting furnace to 740°C, and under the protection of a mixed gas of sulfur hexafluoride and argon, weigh the corresponding mass of magnesium ingots according to the above mass percentage and add them to the preheated crucible. After the magnesium ingot is melted, add bismuth particles and zinc particles, wherein the actual amount of Mg added is 1.05 times the calculated amount, and the actual amount of Bi added is 1.1 times the calculated amount. Then lower the temperature of the vacuum melting furnace to 725°C, and after all the raw materials are melted, stir for 10 minutes in three times, let it stand for 20 minutes after stirring, remove the surface oxides and impurities by slag removal, and then cool to 710°C for casting to obtain an ingot. After the ingot cools, put it into ice water at 4°C for quenching.
[0080] S3. The obtained cylindrical samples were cut into 35 mm in height and 30 mm in diameter, and homogenized in a box-type resistance furnace. After the temperature of the box-type resistance furnace was raised to 500°C, the alloy samples were added and kept warm for 4 hours, and then quenched in 20°C water.
[0081] S4. After homogenization treatment, the alloy sample was placed in a resistance furnace at 200°C for 30 minutes, then placed in an extrusion die and extruded on an extruder to complete the extrusion deformation. The extrusion speed was 1 mm / s and the extrusion ratio was 18:1. The sample was extruded into a rod with a diameter of 7 mm.
[0082] The yield strength of the magnesium alloy material of Comparative Example 3 at room temperature is 179.9MPa, the tensile strength is 236.2MPa, and the elongation is 32.7%. The corrosion rate is 1.88mm / y, and the antibacterial rate against Escherichia coli reaches 70.1%. No dead cells are found in cell fluorescence staining, indicating that Comparative Example 3 is non-toxic to cells.
[0083] In the present invention, mechanical property test, in vitro antibacterial effect test and in vitro cytotoxicity test are carried out on Examples 1-6 and Comparative Examples 1-3. The mechanical property test is carried out according to the national standard GB / T 228.1-2010 "Metallic Material Tensile Test Part I: Room Temperature Experimental Method", and the tensile specimen is processed into a standard tensile specimen along the direction parallel to the extrusion direction. The mechanical property data of the embodiments and comparative examples in the present invention are obtained by stretching. The in vitro antibacterial effect test is carried out according to the national standard GB / T 2591:2003 "Antibacterial Plastic Antibacterial Performance Test Method and Antibacterial Effect", and the magnesium alloy samples of the embodiments and comparative examples of the present invention are co-cultured with Escherichia coli for 24 hours, and the colony count after 24 hours is recorded, and the antibacterial rate is calculated to reflect the antibacterial effect of the embodiments and comparative examples. The in vitro cytotoxicity experiment was conducted in accordance with GB / T 16886.1-2011 “Biological Evaluation of Medical Devices”. Endothelial cells were inoculated on the surface of the magnesium alloy samples of the embodiments and comparative examples of the present invention, and the growth and proliferation of the cells were observed after 72 hours using the fluorescent labeling method. The specific results are shown in Table 2.
[0084] Table 1 Specific chemical composition of materials in Examples 1 to 6 and Comparative Examples 1 to 3 (wt.%)
[0085] Table 2 Specific processing parameters of materials in Examples 1 to 6 and Comparative Examples 1 to 3
[0086] In summary, the present invention adjusts the alloy composition and process parameters to prepare a biomedical magnesium alloy with high toughness, antibacterial effect and non-toxicity, and has high strength and high plasticity, and can be used to make implant devices with complex structures. At the same time, the biomedical magnesium alloy with high toughness, antibacterial effect and non-toxicity prepared by the present invention, especially Example 3, has a significant antibacterial effect, with an antibacterial rate of up to 99.7%. The method provides a simple, fast and efficient technology for processing biomedical magnesium alloy implant materials, which can realize large-scale rapid production and has broad application prospects in implant fields such as orthopedics.
[0087] The present invention discloses a biomedical magnesium alloy having high strength and toughness, antibacterial effect and non-toxicity, which is composed of the following weight fractions: Bi: 0.4%~2.2%, Zn: 0.4%~2.2%, and the rest is Mg and inevitable impurities. The present invention also provides a method for preparing the biomedical magnesium alloy, through microalloying design, high-purity raw materials are selected to prepare magnesium alloy ingots, and then through cutting, homogenization treatment, extrusion deformation, the strength and plasticity of the magnesium alloy are improved simultaneously, and the antibacterial effect of the magnesium alloy is significantly improved. The present invention provides a simple, fast and efficient magnesium alloy implant material processing technology, which can support large-scale and rapid production, and has broad application prospects in the field of implants such as orthopedics.
Claims
1. High-strength, tough, antibacterial and non-toxic medical magnesium alloy, characterized in that: Calculated by mass percentage, it includes the following components: Bi: 0.4%~2.2%, Zn: 0.4%~2.2%, and the rest is Mg.
2. The high-strength, toughness, antibacterial and non-toxic medical magnesium alloy according to claim 1, characterized in that: The chemical composition, by mass percentage, is as follows: Bi: 1.97%, Zn: 2.01%, and the rest is Mg.
3. The method for preparing the high-strength, toughness, antibacterial and non-toxic medical magnesium alloy as claimed in claim 1, characterized in that: The specific steps are as follows: S1. According to the mass percentage, 0.4~2.2% of bismuth particles and 0.4~2.2% of zinc particles are weighed, and the rest is magnesium ingot, and the raw materials are polished to remove the surface oxide film; S2. The crucible is placed in a resistance furnace for preheating, and the magnesium ingot, bismuth particles and zinc particles are added to the preheated crucible, and the crucible is heated until the metal is completely melted, stirred, and then slag is removed after standing, and then the slag is quickly cast after the slag is removed, and after solidification, it is quickly quenched in ice water to obtain a magnesium alloy ingot, and a mixed gas of sulfur hexafluoride and argon is introduced throughout the process; S3. The magnesium alloy ingot is subjected to wire cutting, and then subjected to homogenization heat treatment, followed by quenching in water to obtain a heat-treated magnesium alloy; S4. The heat-treated magnesium alloy is placed in an extruder for extrusion processing, and quenched after extrusion to obtain a medical magnesium alloy.
4. The method for preparing the high-strength, toughness, antibacterial and non-toxic medical magnesium alloy according to claim 3, characterized in that: The purity of the magnesium ingot in S1 is ≥99.99%, the purity of the bismuth particles is ≥99.999%, and the purity of the zinc particles is ≥99.99%.
5. The method for preparing the high-strength, toughness, antibacterial and non-toxic medical magnesium alloy according to claim 3, characterized in that: The S2 is operated under the protection of a mixed gas of sulfur hexafluoride and argon in a ratio of 0.5:99.5 throughout the process. The magnesium ingot, bismuth particles and zinc particles are added to a preheated crucible, and then the resistance furnace temperature is heated to 730-750°C to melt the magnesium ingot, bismuth particles and zinc particles, and stirred for 3-5 times for a total of 8-12 minutes. After stirring, the temperature is controlled at 720-740°C, and the mixture is allowed to stand for 20-30 minutes. The slag is then removed, and casting is performed at 710-720°C. After solidification, the ingot is quenched in ice water at 0-4°C to obtain a magnesium alloy ingot.
6. The method for preparing a biomedical magnesium alloy material having high strength and toughness, antibacterial effect and non-toxicity according to claim 3, characterized in that: The conditions of the homogenization heat treatment in S3 are: 480-500°C, holding time of 4-5h, followed by quenching in water at 10-25°C.
7. The method for preparing the high-strength, toughness, antibacterial and non-toxic medical magnesium alloy according to claim 3, characterized in that: The extrusion processing conditions in S4 are: keeping warm in a box furnace at 200-230° C. for 30-35 min, an extrusion ratio of 18:1, an extrusion speed of 1-2.4 mm / s, and quenching the obtained extruded rod in water at 10-25° C.
8. The use of the high-strength, toughness, antibacterial and non-toxic medical magnesium alloy according to any one of claims 1 to 7, characterized in that: This magnesium alloy is used in bone screws, bone plates, intramedullary nails, bone filling materials, vascular stents, oral repair stents and other devices.